Influence of the cyclic loading of very large number of cycles on the pile capacity - Bekki, Hadj; Tali, Brahim; Canou, Jean; Dupla, Jean-Claude; Bouafia, Ali (Journal of Applied Engineering Science & Technology; Vol 2 No 2 (2016), 2016)
The paper presents a study of the bearing capacity of a pile model in calibration chamber, under a cyclic axial loading, up to very large number of cycles. The experimental study is aimed to the evolution of the bearing capacity of pile obtained after a cyclic loading up to 10 5 cycles. Firstly, we present briefly the experimental device and then the results of cyclic tests performed on the pile model in the calibration chamber.  Several parameters which have a significant influence on the cyclic behavior of piles have been investigated, such as the cyclic displacement amplitude and the density of the soil. The analysis of results indicated that the mechanism of densification of the soil around the pile leads to improve pile capacity.
Keywords: Calibration chamber, Pile model, Soil, Interface, Bearing capacity, Cyclic loading